On the Fundamental Causes of High Environmental Alkalinity (pH ≥ 9): An Assessment of Its Drivers and Global Distribution - Jobbágy, Esteban G.; Tóth, Tibor; Nosetto, Marcelo D.; Earman, Sam (Land degradation & development, 2017)
Very alkaline environments exceeding calcite buffering are globally rare but conspicuous in many sedimentary plains of the World. While the deleterious effects of high alkalinity on soils are well understood, less agreement exists on its causes. We revise these causes to understand these exceptional environments and explain the pervasiveness of calcite buffering elsewhere. We argue that the injection of respired CO2 into stagnant hydrological systems subject to evaporative discharge is the key context for high alkalinization. The evolution of evaporites in nature reaches highly alkaline stages only when excess of (bi)carbonate with respect to divalent cations occurs. In most dry landscapes, evaporating groundwater solutions lose this condition as respired inorganic carbon (recharge zone supply) equilibrates with divalent cations from rocks (whole hydro‐trajectory supply). Groundwater in stagnant landscapes avoids this limitation owing to short/shallow trajectories sustaining (bi)carbonate excess until evaporative discharge zones are reached. Flat sedimentary landscapes that are (i) wet enough to develop stagnation and have shallow water tables but (ii) sufficiently dry to expose them to evaporative concentration should host very alkaline soils. This is confirmed with >9,000 soil profiles from the global WISE database, which shows that profiles with pH ≥ 9 in the top meter are 2·7% globally but 18% in areas with low slope (<0·05%, 25‐km radius, SRTM digital elevation model (SRTM DEM)) and semiarid–subhumid climate (annual precipitation to potential evapotranspiration ratio = 0·2–1, CRU database). Understanding how climate and vegetation change as well as irrigation practices influence hydrological stagnation and evaporative concentration may provide the key to manage very alkaline environments. Copyright © 2017 John Wiley & Sons, Ltd.